Multimodal single-cell analyses of peripheral blood mononuclear cells of COVID-19 patients in Japan - Kashima, Yukie; Mizutani, Taketoshi; Nakayama-Hosoya, Kaori; Moriyama, Saya; Matsumura, Takayuki; Yoshimura, Yoshihiro; Sasaki, Hiroaki; Horiuchi, Hiroshi; Miyata, Nobuyuki; Miyazaki, Kazuhito; Tachikawa, Natsuo; Takahashi, Yoshimasa; et al. (Scientific reports, 2023)
SARS-CoV-2 continues to spread worldwide. Patients with COVID-19 show distinct clinical symptoms. Although many studies have reported various causes for the diversity of symptoms, the underlying mechanisms are not fully understood. Peripheral blood mononuclear cells from COVID-19 patients were collected longitudinally, and single-cell transcriptome and T cell receptor repertoire analysis was performed. Comparison of molecular features and patients’ clinical information revealed that the proportions of cells present, and gene expression profiles differed significantly between mild and severe cases; although even among severe cases, substantial differences were observed among the patients. In one severely-infected elderly patient, an effective antibody response seemed to have failed, which may have caused prolonged viral clearance. Naïve T cell depletion, low T cell receptor repertoire diversity, and aberrant hyperactivation of most immune cell subsets were observed during the acute phase in this patient. Through this study, we provided a better understanding of the diversity of immune landscapes and responses. The information obtained from this study can help medical professionals develop personalized optimal clinical treatment strategies for COVID-19.